Novel bioresorbable stent coating for drug release in congenital heart disease applications. Issue 5 (16th September 2014) - Goodfriend, Amy C.; Welch, Tré R.; Barker, Greg; Ginther, Richard; Riegel, Matthew S.; Reddy, Surendranath Veeram; Wang, Jian; Nugent, Alan; Forbess, Joseph
Abstract: A novel double opposed helical poly‐l ‐lactic acid (PLLA) bioresorbable stent has been designed for use in pediatrics. The aim was to test the PLLA stent biocompatibility. The PLLA stent was immersed into whole pig's blood in a closed loop circuit then fibrin and platelet association was assessed via enzyme‐linked immunosorbent assay. D‐Dimer was valued at 0.2 ± 0.002 ng/mL and P‐selectin 0.43 ± 00.01 ng/mL indicating limited association of fibrin and platelets on the stent. To improve biocompatibility by targeting inflammatory cells, dexamethasone was incorporated on PLLA fibers with two coating methods. Both coatings were poly(l ‐lactide‐ co ‐glycolide) acid (PLGA) but one was made porous with sucrose while the other remained nonporous. There was no change in mechanical properties of the fiber with either coating of PLGA polymer. The total amount of dexamethasone released was then determined for each coating. The cumulative drug release for the porous fiber was significantly higher (∼100%) over 8 weeks than the nonporous fiber (40%). Surface examination of the fiber with scanning electron microscopy showed more surface microfracturing in coatings that contain pores. The biocompatibility of this novel stent was demonstrated. Mechanical properties of the fiber were not altered by coating with PLGA polymer. Anti‐inflammatory drug release was optimized using a porous PLGA polymer. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1761–1770, 2015.